Experimental investigation and numerical prediction for the fatigue life durability of austenitic stainless steel at room temperature - Khairul, M. A.; Sapuan Faris, S. M.; Al-Oqla, F. M.; Zainudin, E. S. (Growing Science, 2019)
This work investigated and predicted the fatigue life durability of Austenitic Stainless Steel 316L due to its importance in plant industries worldwide. Modelling and simulations were performed to clarify the fracture as well as stress distribution using integrated mechanism. Experimental fatigue validations were also carried out to demonstrate the effect of various fatigue life parameters. Various loading conditions with variable load amplitudes were validated utilizing a frequency of 5 Hz and a stress ratio of 0.1. The accuracy of the simulation results were also verified based on the experimental data. High consistencies between the predicted fatigue life and the experimental results were achieved which increases the validity of the built model.